Effects of different sources of β-glucan on pasting, gelation, and digestive properties of pea starch. (February 2023) - Cui, Yanmin; Han, Xuedong; Huang, Xin; Xie, Wanying; Zhang, Xiushan; Zhang, Zuoyi; Yu, Qianhui; Tao, Lu; Li, Tuoping; Li, Suhong
Abstract: The effects of Lentinula edodes β-glucan (LG), yeast β-glucan (YG), and oat β-glucan (OG) on pasting, gelation, and digestive properties of pea starch (PeS) were studied. Because of different molecular weights and spatial conformation, β-glucan interacted differently with PeS. With the increase of molecular weight of OG, YG, and LG, the pasting property and the gelatinization enthalpy (ΔH) of β-glucan-PeS (G-PeS) suspension decreased by rapid viscosity analyzer and differential thermal scanning analysis, respectively, which was consistent with the results of X-ray diffraction; texture parameters of G-PeS gel were increased and the scanning electron microscope furtherly showed that the structure of 0.5% G-PeS gel was more stable. The rheological parameters (energy storage modulus (G′) and loss modulus (G″) of G-PeS were LG-PeS ≈ YG-PeS > OG-PeS. And the blue shift degree of absorption peak in the Fourier transform infrared spectrum of G-PeS gels (1639.09 cm −1, 1639.12 cm −1, and 1637.78 cm −1 ) proved that LG and YG with trihelix structure could form stronger hydrogen bonds with starch granules compared with OG without trihelix structure. In vitro simulated digestion experiments showed that the inhibition degree of β-glucan on the digestion rate of G-PeS was LG > YG > OG. Herein, adding β-glucan to pes starch has a big potential to promote the texture of PeS-based foods and help diabetics control postprandial glucose levels. Graphical abstract: Image 1 Highlights: β-Glucan of oat (OG), yeast (YG) and Lentinula edodes (LG) showed enhanced wrapping effects on pea starch (PeS). LG and YG with trihelix structure could form stronger hydrogen bonds with PeS compared to OG. LG had the better inhibition effect on the digestion rate of PeS than YG and OG.